Conditioned Medium Derived from Notochordal Cell-Rich Nucleus Pulposus Tissue Stimulates Matrix Production by Canine Nucleus Pulposus Cells and Bone Marrow-Derived Stromal Cells - de Vries, Stefan A.H. (Tissue Eng Part A, 2015)
Objectives: Conditioned medium derived from notochordal cell-rich nucleus pulposus tissue (NCCM) was previously shown to have a stimulatory effect on bone marrow stromal cells (BMSCs) and nucleus pulposus cells (NPCs) individually, in mixed species in vitro cell models. The objective of the current study was to assess the stimulatory effect of NCCM on NPCs in a homologous canine in vitro model and to investigate whether combined stimulation with NCCM and addition of BMSCs provides a synergistic stimulatory effect. Methods: BMSCs and NPCs were harvested from chondrodystrophic dogs with confirmed early intervertebral disc (IVD) degeneration. NCCM was produced from NP tissue of nonchondrodystrophic dogs with healthy IVDs. BMSCs or NPCs alone (3×10(6) cells/mL) and NPCs+BMSCs (6×10(6) cells/mL; mixed 1:1) were cultured for 4 weeks in 1.2% alginate beads under base medium (BM), NCCM, or with addition of 10 ng/mL transforming growth factor-β1 (TGF-β1) as a positive control. Beads were assessed for glycosaminoglycan (GAG) and DNA contents by biochemical assays, GAG deposition by Alcian blue staining, and gene expression (aggrecan, versican, collagen 1 and 2, SOX9, A disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5), and matrix metalloproteinase 13 [MMP13]) with real-time quantitative RT-PCR. Results: NCCM increased NPC proliferation, proteoglycan production, and expression of genes associated with a healthy NP-like phenotype. BMSCs also showed increased proteoglycan production under NCCM, but these effects were not observed at the gene level. Combined stimulation of NPCs with NCCM and coculturing with BMSCs did not result in increased proteoglycan content compared to stimulation with NCCM alone. Discussion: NCCM stimulates matrix production by both NPCs and BMSCs and directs NPCs toward a healthier phenotype. NCCM is therefore promising for IVD regeneration and identification of the bioactive components will be helpful to further develop this approach. In the current study, no synergistic effect of adding BMSCs was observed.